Some points regarding the edge-distance-balanced property of the generalized Petersen graphs GP(n, 2). Issue 4 (18th May 2020) - Ezadi, Mahboubeh; Alaeiyan, Mehdi
Abstract: Suppose t ≥ 5 denote a positive integer. a graph G of diameter d is said to be edge-distance-balanced whenever for any pair of vertices u, v of G, the number of edges closer to u than to v is equal to the number of edges closer to v than to u . suppose GP ( n, 2) be generalized Petersen graph. In this article we consider that for any positive integer t ≥ 5, the generalized Petersen graph GP (4 t + 1, 2) GP (4 t + 2, 2) GP (4 t + 3, 2) are not edge-distance-balanced.